Pluralism of goals of proecological architecture - Kobylarczyk, Justyna; Marchwinski, Janusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
This article discusses selected concepts for defining the goals of modern pro-ecological architecture. It highlights a significant diversity of attitudes towards the issue of ecology in architecture. This clear pluralism of goals results from the priorities given to buildings and is the effect of emphasizing individual ecological problems to a various extent. In the present article, it has been demonstrated that two attitudes coexist today: the pro-environmental one and pro-humanistic one, with further variations occurring within the two approaches. Attention was also paid to the evolution of ecological goals in architecture, as well as to threats that may lead to its distortions under the influence of a narrow perception of these issues. The article is cognitive and is based on the analysis of the abovementioned attitudes. It aims at the organization of the knowledge and observations in this area. The authors recognize that a conscious and, above all, the apposite definition of ecological goals provides a foundation for creating architecture in line with the general concept of ​​sustainable development. The authors are inclined to conclude that the contemporary model of a pro-ecological building should be based on balancing pro-humanistic and pro-environmental goals.